Pengembangan Pendekatan Kurikulum K13 di SD/MI - Yessika Destiana lahabu; Abroto (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
The process of teaching and learning activities in current conditions can be carried out by paying attention to several things. The first is to coordinate with the COVID-19 task force regarding whether or not teaching and learning activities can be carried out in schools. As a result of these changes in learning, of course, there are difficulties at every level of education, where previously learning was carried out face-to-face, whereas now they have to do online learning. by government education decisions. This research is library research, where researchers use library research methods by searching for data on web journals, books, and other websites that have the data needed. The research results from the information above start from the K13 curriculum which has core competencies, basic competencies and indicators, and a learning system that has been arranged in such a way starting from the subjects presented, lesson hours on one theme, and the desired final goal, everything is stated in K13 curriculum.